Wizer.me and Socrative as innovative teaching method tools: Integrating TPACK and Social Learning Theory - Narentheren Kaliappen; Wan Nurisma Ayu Ismail; Ahmad Bashawir Abdul Ghani; Dwi Sulisworo (International Journal of Evaluation and Research in Education (IJERE), 2021)
The purpose of this paper is to share a lecturer’s viewpoint on using Wizer.me and Socrative applications as an innovative teaching method integrating TPACK and Social Learning Theory (SLT) at higher education. The applications were used to teach 44 undergraduate students who registered for Cross-Cultural Management course at Universiti Utara Malaysia (UUM). At first, the lecturer used Wizer.me before the class starts and requesting the students to answer several questions before coming to the class. After completing each chapter, the students requested to answer some questions using Socrative application to test their understanding level. The research revealed that at the beginning of the semester, the students not aware of these two applications. However, at the end of the semester, every student familiar with these applications and overall provided positive feedback on the usage of Wizer.me and Socrative application in the teaching and learning process. This study used IntenCheck sentiment analysis software to evaluate the students’ feedback. Student’s opinion on using Wizer.me and Socrative application as an innovative teaching method not explored before at UUM. Therefore, this viewpoint could provide useful insight for university lecturers to use these applications in their teaching and learning process.